2002
DOI: 10.1182/blood.v99.5.1683
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface antigen CD109 is a novel member of the α2 macroglobulin/C3, C4, C5 family of thioester-containing proteins

Abstract: Cell surface antigen CD109 is a glycosylphosphatidylinositol (GPI)-linked glycoprotein of approximately 170 kd found on a subset of hematopoietic stem and progenitor cells and on activated platelets and T cells. Although it has been suggested that T-cell CD109 may play a role in antibodyinducing T-helper function and it is known that platelet CD109 carries the Gov alloantigen system, the role of CD109 in hematopoietic cells remains largely unknown. As a first step toward elucidating the function of CD109, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
172
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(181 citation statements)
references
References 66 publications
7
172
1
1
Order By: Relevance
“…CD109 is a 170-kd glucose-6-phosphate isomerase-linked protein that was recently identified as a member of the ␣ 2 -macroglobulin and the complement C3, C4, and C5 gene family, which are proteins that contain activated thioesters (28). The similarity of CD109 to ␣ 2 -macroglobulin suggests that it may serve as a protease inhibitor in cartilage or may possibly play a role in complement activity.…”
Section: Discussionmentioning
confidence: 99%
“…CD109 is a 170-kd glucose-6-phosphate isomerase-linked protein that was recently identified as a member of the ␣ 2 -macroglobulin and the complement C3, C4, and C5 gene family, which are proteins that contain activated thioesters (28). The similarity of CD109 to ␣ 2 -macroglobulin suggests that it may serve as a protease inhibitor in cartilage or may possibly play a role in complement activity.…”
Section: Discussionmentioning
confidence: 99%
“…The GPI-anchored protein CD109 belongs to the a 2 -macroglobulin family (Lin et al 2002) and binds TGF-b1 with high affinity and other TGF-b isoforms with lower affinity (Tam et al 1998). It also forms a complex with TGF-b signaling receptors and negatively regulates TGF-b signaling (Finnson et al 2006).…”
Section: Cd109mentioning
confidence: 99%
“…In addition, a sequence for the thioester bond (CGEQ) was found (amino acids 923-926 in Figure 1c) (Hofmann et al, 1999). After completing the sequence, it turned out that this cDNA encoded a mouse orthologue of the human CD109 gene, a member of the a 2 -macroglobulin/C3, C4, C5 family that was recently reported (Lin et al, 2002).…”
mentioning
confidence: 99%
“…Lin et al (2002) recently reported the cloning of human CD109 gene that encodes a novel member of the a 2 -macroglobulin/C3, C4, C5 family, including a 2 -macroglobulin-like protease inhibitors and complement proteins. The amino-acid identity between human and mouse genes was approximately 69%.…”
mentioning
confidence: 99%